Identification and Characterization of the ROP GTPase Gene Family in Strawberry and the Positive Role of FveROP4 in Fruit Resistance to Gray Mold - Shuai Zhao; Baode Zhu; Zhijun Zou; Yushan Zhai; Sufeng Liao; Ming Xu; Kunyang Li; Nasir Mehmood; Xiong Liao (Agronomy)
ROP small GTPases function as signaling hubs that mediate various physiological processes, including plant defense. Their specific roles in strawberry resistance against gray mold remain uncharacterized. In this study, we identified 53 ROP genes across the genomes of six Rosaceae species. Based on sequence homology, they were classified into three distinct phylogenetic clades. Detailed analysis of FveROP proteins revealed the presence of highly conserved catalytic G-domains, which are essential for their GTPase activity. By conducting transient overexpression experiments in strawberry fruits challenged with the gray mold pathogen Botrytis cinerea, we investigated the impact of the FveROP4 gene on disease resistance. The overexpression of both wild-type and constitutively active forms of FveROP4 enhanced resistance against B. cinerea infection. Subsequent analysis revealed that overexpression of FveROP4 and FveCAROP4 genes led to increased accumulation of reactive oxygen species. Moreover, FveROP4 was localized on the plasma membrane, where it interacted directly with FveRBOHF1, corroborating the results obtained through yeast two-hybrid and luciferase complementation imaging assays. The study findings may provide valuable insights for investigating the mechanisms of ROP signaling in regulating the immune response in strawberries and could significantly contribute to strawberry breeding programs aimed at developing new cultivars with enhanced fruit shelf life.